2016
DOI: 10.1038/srep28176
|View full text |Cite
|
Sign up to set email alerts
|

Arm Selection Preference of MicroRNA-193a Varies in Breast Cancer

Abstract: MicroRNAs (miRNAs) are short noncoding RNAs derived from the 3′ and 5′ ends of the same precursor. However, the biological function and mechanism of miRNA arm expression preference remain unclear in breast cancer. We found significant decreases in the expression levels of miR-193a-5p but no significant differences in those of miR-193a-3p in breast cancer. MiR-193a-3p suppressed breast cancer cell growth and migration and invasion abilities, whereas miR-193a-5p suppressed cell growth but did not influence cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
99
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(102 citation statements)
references
References 43 publications
(91 reference statements)
3
99
0
Order By: Relevance
“…One of these, MIR193A, encodes two mature miRNAs with well-known tumour suppressor functions; miR193a-3p and miR193a-5p are generated from the primary transcript by means of several maturation steps. The expression preference of miR193a-5p and miR193a-3p is likely to be determined by the Ago protein (reviewed by Tsai et al 2016). According to the mirbase database (http://www.mirbase.org/), miR193a-3p is more abundantly expressed in human tissues than miR193a-5p.…”
Section: Co-deleted Genes With the Potential To Influence The Clinicamentioning
confidence: 99%
See 2 more Smart Citations
“…One of these, MIR193A, encodes two mature miRNAs with well-known tumour suppressor functions; miR193a-3p and miR193a-5p are generated from the primary transcript by means of several maturation steps. The expression preference of miR193a-5p and miR193a-3p is likely to be determined by the Ago protein (reviewed by Tsai et al 2016). According to the mirbase database (http://www.mirbase.org/), miR193a-3p is more abundantly expressed in human tissues than miR193a-5p.…”
Section: Co-deleted Genes With the Potential To Influence The Clinicamentioning
confidence: 99%
“…According to the mirbase database (http://www.mirbase.org/), miR193a-3p is more abundantly expressed in human tissues than miR193a-5p. Several studies have indicated that miR193a-3p suppresses tumour development by silencing multiple target genes including SRSF2 , HIC2, HOXC9, PSEN1, LOXL4, ING5 , KIT , PLAU and MCL1 (Tsai et al 2016). miR193a-3p has been found to be down-regulated by hypermethylation in oral squamous cell carcinoma cell lines (Kozaki et al 2008), non-small cell lung cancer (Heller et al 2012; Wang et al 2013; Liang et al 2015; Ren et al 2015), bladder cancer (Deng et al 2014; Lv et al 2014; Li et al 2015), hepatocellular carcinoma (Salvi et al 2013), BRAF mutation-positive malignant melanoma (Caramuta et al 2010), acute myeloid leukaemia (Xing et al 2015) and pleural mesothelioma (Williams et al 2015).…”
Section: Co-deleted Genes With the Potential To Influence The Clinicamentioning
confidence: 99%
See 1 more Smart Citation
“…miR-193a, which consists of miR-193a-3p and miR-193a-5p, is one of the miRNAs involved in carcinogenesis. miR-193a-3p plays essential roles in the multi-chemoresistance of bladder cancer [10], epithelial ovarian cancer [11], breast cancer [12], colorectal cancer [13] and lung cancer [14]. However, although several studies indicating that miR-193a-3p is closely related to tumourigenesis have been published, the detailed roles of miR-193a-3p in the initiation and progression of NSCLC remain largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…This is an open-access article distributed under the terms of the Creative Commons Attribution-NonCommercial 4.0 International License (http://creativecommons.org/licenses/by-nc/4.0/) which permits copy and redistribute the material just in noncommercial usages, provided the original work is properly cited analysis software revealed that miR-193b targets 5genes in Wnt and TGF-b signaling pathways (11)(12)(13)(14). Although miR193b sequence shares 88% identity with miR-193a, it is encoded by a separate gene with distinct regulation (15,16). miR-193b has been implicated as a tumor suppressor in breast cancer.…”
Section: Introductionmentioning
confidence: 99%